Students’ Understanding of Algebraic Factorization Problems based on Their Meaning of The Equals Sign - Lia Ardiansari; Didi Suryadi; Dadan Dasari (IKIP Siliwangi, 2022)
This paper reports an investigation of students' understanding of the concept of factorization in algebraic forms learned in secondary school. A total of 31 grade 8th junior high school students were selected by purposive sampling technique as respondents in this case study research. The case study approach is considered in accordance with the objectives of this study, namely obtaining in-depth knowledge of student problems, knowing the causes of these problems, and efforts that can be made to help overcome them. Methods of collecting data using written tests, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results showed that there was a misunderstanding of students' concepts about the concept of factorization in algebraic forms so that they experienced difficulties in